Forensic Challenges in Diagnosing Meningococcal Sepsis Postmortem - Uswa Zaib, Asiya Fazal, Farhat Sultana, Fariha Tariq, Wasiq Ahmed, Muhammad Anwar Sibtain Fazli (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Neisseria meningitidis septicemia remains a critical cause of sudden death, yet postmortemdiagnosis is frequently obscured by nonspecific autopsy findings and postmortem bacterialovergrowth. In a retrospective case control forensic analysis of 25 suspected meningococcal sepsiscases, conventional cultures yielded confirmatory results in only